The hypertension cascade of care in the midst of conflict - Abu Hamad, Bassam A. (2022)
Funding Information: This study was jointly funded by the UK’s Department for International Development (DFID), the Medical Research Council (MRC), the Economic and Social Research Council (ESRC) and Wellcome Trust’s Health Systems Research Initiative (HSRI) (MR/S012877/1). Publisher Copyright: © 2022, The Author(s).